ANALISIS PENGARUH LEVERAGE (SUSTAINABLE REPORTING, SALES GROWTH DAN DEBT TO EQUITY RATIO) TERHADAP KINERJA RETURN ON ASSETS (ROA) DAN RETURN ON EQUITY (ROE) - Nabilatus Salma; Anwar Hariyono (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2025)
This study aims to analyze the influence of Sustainability Reporting (SR), Sales Growth (SG), and Debt to Equity Ratio (DER) on Return on Assets (ROA) and Return on Equity (ROE). A quantitative approach was employed, with a sample of 30 companies listed on the Indonesia Stock Exchange (IDX) from 2019–2023, selected using purposive sampling. The results indicate: (1) SR has a positive effect on ROA by enhancing operational efficiency and corporate reputation; (2) SG does not consistently influence ROA due to potential mismatches between revenue growth and cost management; (3) DER dynamically impacts ROA, where optimal leverage improves profitability, while excessive debt may reduce ROA. Furthermore, (4) SR positively affects ROE as ESG practices strengthen investor confidence; (5) SG has no significant impact on ROE since net profit depends on capital efficiency rather than sales growth alone; (6) DER enhances ROE through financial leverage, provided debt is managed prudently. The findings highlight the importance of SR and balanced debt management for financial performance, whereas SG requires complementary efficiency strategies. Companies are advised to integrate sustainability practices and optimize leverage for long-term profitability.